CNS efficacy parameters of combination antiretroviral therapy in chronic HIV infection: A multi-voxel magnetic resonance spectroscopy study - Brkic, Snezana; Veres, Benjamin; Thurnher, Majda M.; Boban, Jasmina; Radovanovic, Bojan; Tomic, Slavica; Kozic, Dusko (Frontiers in Neurology, 2023)
This study aimed to determine the correlations of combination antiretroviral therapy (cART) efficacy parameters in the central nervous system (CNS) with a neurometabolic profile on magnetic resonance spectroscopy (MRS) in virally suppressed, neurologically asymptomatic HIV+ individuals. In total, 32 HIV+ individuals on stable cART with an average age of 41.97 ± 10.12 years and with available clinical data, CNS penetration effectiveness (CPE), and monocyte efficacy (ME) scores underwent multi-voxel MRS. The parameters of neuronal number/function (NAA/Cr), membrane turnover (Cho/Cr), and glial proliferation (mI/Cr) were analyzed in supratentorial white and gray matter. Correlations of CPE and ME with neurometabolic ratios were performed using Pearson's correlation test. Statistical significance was set at p < 0.05. A strong positive correlation was observed between Cho/Cr and CPE in the left parietal subcortical white matter (r = 0.577, p = 0.001). A strong positive correlation between NAA/Cr and ME was obtained in the left (r = 0.521, p = 0.003) and the right (r = 0.494, p = 0.005) posterior cingulate. A strong negative correlation between ME and Cho/Cr ratios was observed in the right frontal deep white matter (r = −0.569, p = 0.001). Indices designed to assess cART efficacy in CNS failed to present significant correlations with the neurometabolic profile obtained using MRS. There is a need to define more potent non-invasive tools for neuroinflammation assessment given the prolonged life expectancy in the HIV+ population.